Effects of Gender of Reciprocal Chromosomal Translocation on Blastocyst Formation and Pregnancy Outcome in Preimplantation Genetic Testing - Song, Hui; Shi, Hao; Yang, En-tong; Bu, Zhi-qin; Jin, Zi-qi; Huo, Ming-zhu; Zhang, Yi-le (Frontiers in Endocrinology, 2021)
Objective To determine the effect of gender of reciprocal chromosomal translocation on blastocyst formation and pregnancy outcome in preimplantation genetic testing, including different parental ages. Methods This was a retrospective cohort study that enrolled 1034 couples undergoing preimplantation genetic testing-structural rearrangement on account of a carrier of reciprocal chromosomal translocation from the Reproductive Medicine Center of the First Affiliated Hospital of Zhengzhou University from January 2015 to December 2019. Group A represented 528 couples in which the man was the carrier of reciprocal translocation and group B represented 506 couples in which the woman was the carrier of reciprocal translocation. All patients were divided into two groups according to their age: female age<35 and female age≥35. Furthermore, the differences in blastocyst condition and pregnancy outcome between male and female carriers in each group were further explored according to their father’s age. Results The blastocyst formation rate of group A (55.3%) is higher than that of group B (50%) and the results were statistically significant (P<0.05). The blastocyst formation rate of group A is higher than that of group B, no matter in young maternal age or in advanced maternal age (P<0.05). The blastocyst formation rate in maternal age<35y and paternal age<30y in group A(57.1%) is higher than that of Group B(50%); Similarly, the blastocyst formation rate in maternal age≥35 and paternal age≥38y(66.7%) is higher than that of Group B(33.3%)(all P<0.05). There was no difference in fertilization rate, aeuploidy rate, clinical pregnancy rate, miscarriage rate and live birth rate between Group A and Group B. Conclusion When the carrier of reciprocal translocation is male, the blastocyst formation rate is higher than that of female carrier. While there is no significant difference between the two in terms of fertilization rate, aeuploidy rate, clinical pregnancy rate, miscarriage rate and live birth rate.